The Impact of the Amendment to Art. 115 of the Environmental Protection Law on The Right of a Resident to Demand that the Noise Level be Checked - Bandarzewski, Kazimierz (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Noise is an element of the environment and is increasingly important for the proper functioning of a human being. Regulation of Art. 115a paragraph. 1 of the Environmental Protection Law narrows the sources of noise covered by this regulation. The procedure for issuing a decision on the permissible noise level consists of two stages: one of them is carrying out control activities allowing to determine the exceeded level of such emission. The legislator didn’t grant the resident an effective demand to initiate control proceedings in this respect. As a result of the amendment to Art. 115a paragraph. 1 of the Environmental Protection Law, which entered into force on 23 of September 2021, was to eliminate the government administration from among the authorities obliged to carry out control proceeding. Thus, the possibility of initiating disputes over the competence of the authority responsible for carrying out the inspection was significantly limited. Another effect of this amendment is also the limitation of government administration expenses for carrying out control activities and transferring these expenses to the county self-government.